Transnational Traditions : New Perspectives on American Jewish History - Kahn, Ava F. (Book collections on Project MUSE., 2014)
Shows the extensive bonds that flourished among Jews around the world, linked through the United States, the most popular destination spot in the great age of migration. The book proves both the fluidity of national boundaries and the centrality of the United States in modern Jewish history.